Perubahan Karakter Religius Masyarakat melalui lensa Difusi Budaya (Studi Kasus: Penyebaran Nilai-nilai Religius di Desa Taman Kecamatan Sumbermalang Kabupaten Situbondo) - Akhti Syarifah; Umar Manshur (CV Edujavare Publishing, 2023)
The research method used is a qualitative approach, case study type. This research activity places more emphasis on concepts and processes. Data collection techniques through observation, interviews and documentation. Meanwhile, to analyze the data using the Miles and Huberman method of analysis, namely data reduction, data display and verification. With this method, it is hoped that researchers will obtain accurate data. The results of this research show that (1) The form of change in the religious character of society through the lens of cultural diffusion. Case study of the spread of religious values in Taman village, Sumbermalang subdistrict, Situbondo district, seen in terms of (a) education and learning (b) ethical changes (c) participation in religious activities (d) social and moral changes. (2) The inhibiting and supporting factors in changing the religious character of society through the lens of cultural diffusion, case study: the spread of religious values in Taman village, Sumbermalang subdistrict, Situbondo district. Inhibiting factors are (a) social tension and conflict (b) negative community response. Supporting factors are (a) family (b) social mobility (c) communication and technology (d) interaction with other organizations